Peace a world history - Adolf, Antony (Polity, 2009)
"This book is essential reading for students, scholars, policy-shapers, activists and general readers involved with how present forms of peace and peacemaking have been influenced by those of the past, and how future forms can benefit by taking these into account."--Jacket